The Digital HR Revolution: Rethinking Employee Satisfaction In Tech-Driven Work Environments - Herlissha, Novita; Noviyanti, Indah; Wibawa, Dian Prihardini; Wulandari, Ayu (Jurnal Mebis, 2025)
In the wake of digital transformation, the integration of Human Resource (HR) technologies has become increasingly prevalent across various sectors. This study investigates the influence of three key factors—perceived ease of use, user comfort, and organizational support—on employee satisfaction within tech-driven work environments. The research was conducted across multiple organizations that have adopted digital HR platforms. Using a quantitative approach, data were collected through structured questionnaires distributed to 97 employees who actively utilize digital HR systems. In this study, the data were processed using SmartPLS 4.0. The findings reveal that all three independent variables significantly contribute to employee satisfaction. Perceived Ease of Use has a positive and significant effect on employee satisfaction. Perceived Usefulness has a positive and significant effect on employee satisfaction. Organizational support has a positive and significant effect on employee satisfaction.